Ethnotaxonomical Study of Mole Crab (Crustacea:Hippoidea) on Coastal Community of Cilacap - Dian Bhagawati; Sutrisno Anggoro; Mohammad Zainuri; Lachmudin Sya'rani (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Local wisdom is a cultural heritage that needs to be preserved. The Cilacap’s coastal communities have traditional taxonomy knowledge that hasn’t been informed, especially about mole crab. This study aimed to explore the ethnotaxonomy knowledge of sand crabs (Crustacea: Hippoidea) in Widarapayung coastal communities. The purposive snowball sampling was used for the method, followed by observation and semi-structured interviews with 30 respondents. Data were analyzed descriptively based on observations and interviews. The results showed that the coastal communities in Widarapayung tourist areas could be divided into five groups, namely catchers, collectors, processors, traders, and consumers. The catcher was able to recognize and describe three types of sand crabs based on the shape of the body and their catchment areas. Captured crabs had the local name of ‘yutuk jambe’ (Emerita emeritus Linnaeus 1767), the appellation was based on carapace shape that resembled the shape of areca fruit; ‘Yutuk bathok’ (Hippa adactyla Fabricius 1787), had the carapace shape resembling a coconut shell, and ‘yutuk Kethek’ (Albunea symmysta Linnaeus 1758), had ornaments on the carapace surface similar with a monkey face, there were dense setae on the edge of the carapace, spiny long antennas and aggressively pinch when captured. The knowledge and skills of sand crabs classification and local name entitlement acquired by the people were in accordance with the Berlin’s model. How to CiteBhagawati, D., Anggoro, S., Zainuri, M. Sya’rani, L. (2016). Ethnotaxonomical Study of Mole Crab (Crustacea:Hippoidea) on Coastal Community of Cilacap. Biosaintifika: Journal of Biology Biology Education, 8(2), 222-230.